Service provision and utilisation in German paediatric primary care practices during public health crises: protocol of the mixed-methods COVID-19 PedCare Study - Falkenstein, Lina; Eckel, Nathalie; Kadel, Simone; König, Jochem; Litaker, David; Eichinger, Michael (BMJ open, 2022)
Introduction Public health crises such as pandemics can cause serious disruptions to the utilisation and provision of healthcare services with negative effects on morbidity and mortality. Despite the important role of paediatric primary care in maintaining high-quality healthcare services during crises, evidence about service utilisation and provision remains limited especially in Germany. This study, therefore, explores the utilisation and provision of paediatric primary care services during the ongoing COVID-19 pandemic and their barriers and facilitators. - Methods and analysis The study uses a convergent mixed-methods design and comprises online surveys to parents, adolescents and primary care paediatricians (PCPs) and semistructured interviews with parents and PCPs. We recruit parents and adolescents from paediatric primary care practices and PCPs via email using mailing lists of the German Professional Association of Paediatricians and the German Society of Ambulatory Primary Care Paediatrics. The parent and adolescent surveys assess, inter alia, the utilisation of paediatric primary care services and its correlates, aspects of parental and child health as well as socioeconomic characteristics. The PCP survey investigates the provision of paediatric primary care services and its correlates, aspects of PCP health as well as sociodemographic and practice characteristics. The semistructured interviews with parents and PCPs explore several aspects of the online surveys in more detail. We use descriptive statistics and generalised linear mixed models to assess service utilisation and provision and specific correlates covered in the online surveys and apply qualitative content analysis to explore barriers and facilitators of service utilisation and provision more broadly in the semistructured interviews. We will integrate findings from the quantitative and qualitative analyses at the interpretation stage. - Ethics and dissemination The study was approved by the Medical Ethics Review Board of the Medical Faculty Mannheim at Heidelberg University (2020-650N). Study results will be published in journals with external peer-review.
Gesehen am 01.02.2023